Psychopathy, risk taking and attention: A differentiated test of the somatic marker hypothesis - Lösel, Friedrich; Schmucker, Martin (Journal of Abnormal Psychology, 2004)
A. R. Damasio's (1994) somatic marker hypothesis relates psychopathy to deficits in the ventromedial prefrontal cortex. Using the gambling task (A. Bechara, A. R. Damasio, H. Damasio, & S. Anderson, 1994), the authors tested this premise and the role of attention as a moderator. Forty-nine male prison inmates were assessed with the Psychopathy Checklist - Revised (R. D. Hare, 1991), the gambling task, and standardized tests on attention-concentration, and intelligence. Results revealed no general relation between psychopathy and gambling task performance. However, psychopathic inmates with low attention scores gambled worse than did the attentive ones. They also had more previous convictions. In nonpsychopathic individuals, attention had no impact. Different processing strategies for psychopathic and nonpsychopathic individuals are proposed to explain these findings.